Responding to hate incidents on university campuses: benefits and barriers to establishing a restorative justice programme - Walters, Mark Austin (Contemporary justice review, 2021)
This study examines staff and student perspectives of the use of restorative justice approaches to respond to student-on-student hate crime, hate incidents, and hate speech on university campuses. It draws on qualitative data collated over a one-year period, during the design and establishment of a restorative programme entitled ‘Restore Respect’ at two UK universities. Highlighting examples of students’ experiences of prejudice and hate across the two universities, we outline some of the key barriers to reporting associated with conventional university responses, as well as staff and student views of establishing a new restorative approach to addressing incidents. While early-stage evaluation revealed certain cultural and institutional barriers and limitations to the establishment and operation of a restorative programme, the majority of staff and students viewed it as an effective way of addressing hate-based conduct that would provide greater opportunity for more positive interventions and outcomes. The paper concludes by arguing for a renewed effort to move beyond standard institutional responses to student experiences of hate and prejudice at university through the adoption of restorative, needs-centred approaches.